Mejoramiento de la eficiencia energética en un proceso de cadena de frio en una industria de alimentos (2021)
The improvement in the energy efficiency of the cold chain allows saving in energy, economic costs and reducing greenhouse gas emissions into the atmosphere. This project studies the cold control process in a food industry from the energy point of view, analyzes the energy consumption that occurs in the processes, proposes several actions to reduce the use of energy, applies these actions and finally it measures consumption in order to determine the savings in this system. The energy consumption analysis was carried out, finding an average annual consumption of 8200 kWh. By jointly analyzing all energy demands and relating them to production, a consumption baseline was established where the fixed consumption is 6646 kWh and that for each production unit there is a consumption of 0.124 kWh of energy. It was determined that the electrical consumption of approximately 85% comes from the consumption of refrigeration system compressors. A review was carried out determining good operating practices and technological changes that combined can yield savings between 15% and 20%. The savings potential in the implementation of the proposals was determined, starting from the baseline consumption, determining that the fixed consumption can reach 6234 kWh and 0.124 kWh of energy for each production unit. The above represents 6.2% of real consumption savings of the company, which can be achieved with the implementation of good practices and technological changes. Finally, a costing of the implementation to date of good operating practices and technological changes was carried out, which can be assumed with the savings calculated in the implementation proposal. The project could be carried out thanks to the collaboration of the company despite the pandemic situation.